Wiring the Past: A Network Science Perspective on the Challenge of Archeological Similarity Networks - Prignano, Luce; Morer, Ignacio; Diaz-Guilera, Albert (Frontiers in Digital Humanities, 2017)
Nowadays, it is a common knowledge that scholars from different disciplines, regardless of the specificities of their research domains, can find in network science a valuable ally when tackling complexity. However, there are many difficulties that may arise, starting from the process of mapping a system onto a network which is not by any means a trivial step. This paper deals with those issues inherent to the specific challenge of building a network from archaeological data, focusing in particular on networks of archaeological contexts. More specifically, we address technical difficulties faced when constructing networks of contexts or sites where past interactions are inferred based on some kind of similarity between the corresponding assemblages (Archaeological Similarity Networks or ASN). We propose a basic characterization in formal terms of ASN as a well defined class of networks with its own specific features. Throughout the paper, we devote special attention to the problem of quantifying the similarity between sites, especially in relation with the ubiquitous issues of data incompleteness and the reliability of the inferred ties. We argue that, generally speaking, human past studies are quite disconnected from the rest of interdisciplinary applications of network science and that this prevent this field from fully exploiting the potential of such methods. Our goal is to give hints about which are the interesting questions that archaeological applications put on the table of networks scientists